A study protocol: a community pharmacy-based intervention for improving the management of sleep disorders in the community settings - Mohamad Noor, Zaswiza; Smith, Alesha J.; Smith, Simon S.; Nissen, Lisa M. (BMC Health Services Research, 2014)
Background Sleep disorders are very common in the community and are estimated to affect up to 45% of the world’s population. Pharmacists are in a position to give advice and provide appropriate services to individuals who are unable to easily access medical care. The purpose of this study is to develop an intervention to improve the management of sleep disorders in the community. The aims are– (1) to evaluate the effectiveness of a community pharmacy-based intervention in managing sleep disorders, (2) to evaluate the role of actigraph as an objective measure in monitoring certain sleep disorders and (3) to evaluate the extended role of community pharmacists in managing sleep disorders. This intervention is developed to monitor individuals undergoing treatment and overcome the difficulties in validating self-reported feedback. Method/design This is a community-based intervention, prospective, controlled trial, with one intervention group and one control group, comparing individuals receiving a structured intervention with those receiving usual care for sleep-related disorders at community pharmacies. Discussion This study will demonstrate the utilisation and efficacy of community pharmacy-based intervention to manage sleep disorders in the community, and will assess the possibility of implementing this intervention into the community pharmacy workflow. Trial registration Australian New Zealand Clinical Trial Registry: ACTRN12612000825853